Intrathecal immunoglobin synthesis and its role in patients with neurosyphilis - Huang, Xiyue; Ying, Shanshan; Luo, Lan; Li, Lixin; Li, Dongdong; Xie, Yi (Frontiers in Public Health, 2022)
Background: Proteins intrathecal synthesis (ITS) occurs in various central nervous system disorders, but there are rare quantitatively studies focusing on the ITS for neurosyphilis (NS) in south-west China. We made a study to quantitatively assessment the ITS in NS patients and to investigate the association between ITS and the stages of NS. Methods: CSF-serum specimen pairs from 152 patients (66 NS and 76 non-NS/syphilis) were collected for CSF routine and sera tests. And NS group was divided into slight and severe subgroups according to NS stages. Three formulas for quantitative determination of intrathecal synthesis characterizing this collective were calculated, including Ig index (QIg/Qalb), Ig extended index (Ig_EI) and Intrathecally synthesized (IgIF). QTPPA /QIgG was used as antibody index (AI=Q specific Ig /QIgG). Results: Compared with the N-NS group, the NS group had significantly higher sero_TRUST titres (1:16, 1:1 1:256), sero_TPPA titters (1:163840,1:1280 1:13107201), the total protein (MTP) and CSF_Igs (p<0.05), but the ALB level was not elevated. For the NS group, intrathecal Ig synthesis can be found using all three formulas. The pattern of Ig intrathecal synthesis is IgIF-G (48.62%)> IgIF-A= IgIF-M(p <0.05), with the dominant intrathecal fraction is IgG(median,48.62%), which is also verified by QIgG>Qalb>QIgM=QIgA. In the slight group, intrathecal fractions of IgM (4 out of 20 cases was >0) and IgG (16 out of 20>0) are lower than intrathecal fractions of IgM (19 out of 35 cases was >0) and IgG (33 out of 38 was >0) in the severe group(p<0.05). The AUC of CSF_TPPA index antibody index was 0.867(0.792,0.922), with its optimal cut-off points 0.81, providing a sensitivity of 88.91% and specificity of 84.62%. Conclusions: For NS patients, the dominant intrathecal synthesis pattern is IgG and patients with a parenchymateous type of disease is associated with intrathecal IgG and IgM fraction. Specific anti-Treponema pallidum response is a new promising tool highly specific for NS diagnosis.